NU AND NATIONALISM: A Study of KH. Achmad Shiddiq’s Trilogy of Ukhuwah as an Effort to Nurture Nationalism Spirit of Indonesian Muslims - Ali Mursyid Azisi, Ali Mursyid Azisi; Agoes Moh. Moefad (Islamuna: Jurnal Studi Islam, 2022)
ABSTRACT This article examines how the principles of Nahdlatul Ulama are related to the spirit of nationalism by analyzing the concept of the ukhuwah trilogy that was initiated by KH. Ahmad Siddiq, Jember. The ukhuwah trilogy consists of ukhuwah islamiyyah (to establish brotherhood with fellow Muslims), ukhuwah wathaniyyah (to establish brotherhood with fellow citizens), and ukhuwah basyariyyah (to establish brotherhood on the basis of fellow humans). The research method used in this research was qualitative descriptive analysis by utilizing primary and secondary literature sources. The analytical knife in this article borrowed Alvin L. Bertrand’s role theory, where the role of Kiai Achmad Shiddiq was so great in instilling brotherhood, nationalism or the spirit of nationalism in Indonesia without discriminating against culture, ethnicity, race, language, and even religion. The results of this study shows that the trilogy concept of ukhuwah is in accordance with Islamic principles, but is also important to be presented to the public in order to improve the quality of harmonious religion while instilling nationalism towards Indonesian Muslims. The prime goal is the common good. The benefit of this research is that it serves as an additional sub-material for academia (lecturers, students), religious leaders, and even the general public to further explore the excellent thoughts of an NU figure named KH. Ahmad Siddiq. ABSTRAK Artikel ini mengkaji tentang bagaimana prinsip Nahdlatul Ulama terkait semangat nasionalisme dengan menganalisis konsep trilogi ukhuwah yang dicetuskan oleh KH. Achmad Shiddiq, Jember. Trilogi ukhuwah terdiri dari ukhuwah islamiyyah (menjalin persaudaraan dengan sesama pemeluk Islam), ukhuwah wathaniyyah (menjalin persaudaraan dengan sesama anak bangsa), serta ukhuwah basyariyyah (menjalin persaudaraan atas dasar sesama manusia). Metode yang digunakan dalam penelitian ini adalah kualitatif analisis deskriptif dengan memanfaatkan sumber literatur primer dan sekunder. Pisau analisis dalam artikel ini meminjam teori peran Alvin L. Bertrand, di mana peran Kiai Achmad Shiddiq begitu besar dalam menanamkan sikap persaudaraan, nasionalisme atau spirit kebangsaan di Indonesia tanpa membeda-bedakan budaya, suku, ras, bahasa, bahkan agama. Hasil penelitian ini yaitu konsep trilogi ukhuwah selain sesuai dengan prinsip Islam, namun juga penting untuk dimunculkan ke muka publik dalam rangka meningkatkan kualitas beragama yang harmonis sekaligus menanamkan sikap nasionalisme terhadap muslim Indonesia. Tujuan besarnya bermuara pada kemaslahatan bersama. Manfaat penelitian ini adalah sebagai tambahan sub materi bahan ajar dan belajar bagi para akademisi (dosen, mahasiswa), agamawan, bahkan masyarakat umum, untuk lebih lanjut menggali pemikiran KH. Achmad Shiddiq.